An Analysis of Toulmin Elements in Indonesian Male and Female EFL Learners' Argumentative Writing - Ardi Nugroho; Rex Stardy (Universitas Muhammadiyah Semarang, 2023)
Argumentative writing is an essential aspect of students’ academic life. Students are commonly required to produce this type of writing as it reflects their ability to think logically and critically. Nevertheless, it may prove to be quite challenging for students, especially for Indonesian EFL learners as they may not be accustomed to writing this kind of text in English. There are some specific elements that must be present for a work to be considered a good argumentative writing, and these elements may be difficult to formulate when writing in another language. To understand the elements of an argumentative writing, one model that is commonly used is the one proposed by the contemporary British philosopher Stephen Toulmin, i.e., the Toulmin’s Argument Pattern (TAP). Some of the key elements highlighted in this model include claim, reasons, evidence, warrants, and rebuttals. Although there have been several studies that focused on the implementation of this model to analyze argumentative writings, not many have directly compared the writings of Indonesian male and female EFL learners. Hence, this study is an attempt to explore how male and female learners from Indonesia produce argumentative writings. More specifically, whether they utilize the elements of argument structures similarly or differently. The data is taken from the International Corpus Network of Asian Learners of English (ICNALE), with a total of 30 pieces of writing that are analyzed. This is divided evenly between the two groups, i.e., 15 writings from male learners and 15 writings from female learners. The data is analyzed qualitatively as no specific calculations are involved when comparing the results from both groups. The findings reveal that only two of the six elements are employed by the learners in their writings, and that there are some similarities and differences in the way the male and female learners utilize the elements in their paragraphs.